Pengaruh Kombinasi Pasir Vulkan, Zeolit, dan Air Laut Terhadap Sifat Kimia Tanah dan Produksi Padi Varietas Lokal di Lahan Gambut Dataran Tinggi Toba - Juriaman Purba; Sarifuddin Sarifuddin; Bintang Sitorus (Universitas Sumatera Utara, 2015)
The objective of this research is to study the effect of combination of volcano sand, zeolite, and sea water to soil chemical properties and the production of rice plant local varieties. This research was conducted in highland peat, village of Hutabagasan Sub District of Dolok Sanggul Distric Humbang Hasundutan North Sumatra. This research used non factorial RAK with four treatments, those are G0 (control), G1 (volcano sand 5 kg), G2 (5 kg + volcano sand sea water 2.5 L), G3 (volcano sand sea water 5 kg + 2.5 L + zeolite 1 kg) and 3 replicants. The results showed that the addition of volcano sand 5 kg + sea water 2,5 L + zeolite 1 kg decreased the pH of the soil, K - exchange, Ca - exchange and percentage base saturation, increased the value of the electrical conductivity (EC), Na - exchange, Mg - exchange. The addition of volcano sand 5 kg + sea water 2,5 L + zeolite 1 kg decrease dry weight of the plant and the number of grains per panicle.Keywords: volcano sand, zeolite, sea water, highland peat soil, Rice